Islam di Thailand - Sanurdi Sanurdi (LPPM IAIN Sorong, 2018)
In the history Islam has existed in Thailand since the 13th century. Muslims have been active in trade and administration in the Thailand kingdom. However, in its development, as a minority, there was conflict due to discrimination and intimidation. In 2000 the percentage of religion in Thailand was Buddhist (95%), Islam (4%), Christian (0.6%), and other religions (0.4%). This paper seeks to examine the existence of Islam and the problems of Muslims as a minority in Thailand. In general, the Muslim population in Thailand is divided into two groups, namely Malay Muslims and Thai Muslims. The majority of Muslims are in the Southern part of Thailand, especially in Pattani area so they are often referred to as Muslim Patani Darussalam or Patani Raya which is closer to Malay. While the Thai Muslims are in the Middle and North that includes the descendants of Iranian Muslims, Champa, Indonesia, India, Pakistan, China, and Malay. Problems faced by Muslims in Thailand are more commonly experienced by Malay Muslims or Pattani in southern Thailand. They are regarded as Khaek (guests or foreigners), a negative prejudice. Malay language and names are prohibited from being used in public institutions, such as schools and government agencies. This resulted in the emergence of Pattani's reaction and resistance to the part of Southern Thailand to obtain special autonomy, even to separatists. Finally, in early 2004 there were several incidents and riots occurring in Southern Thailand, especially in Narathiwat, Yala, and Pattani. This conflict occurs because the demands of the separatist movement and the government act hard against them in militaristic ways, on the other hand people are also dissatisfied with government discrimination as well as violence actions separatist movement. This is exacerbated and worsened by USA intervention in the conflict under the pretext of fighting Islamic separatist violence.